Validity Test of Electronic Student Worksheets (e-LKPD) Based on Scientific Processing Skills - Suhardi Aldi; Adnan Adnan; Ismail Ismail (Jurnal Pendidikan Biologi, 2022)
Various types of teaching materials used by educators. One of them is the electronic student worksheet or e-LKPD. The teaching materials must go through a validity test. The purpose of this study was to test the level of validity of the e-LKPD based on science process skills. This research is research and development or research and development. This study refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The product in this study, namely e-LKPD based on science process skills, was validated by 3 expert validators. The instrument in this study was a product validation questionnaire. The data obtained using the developed instrument, then analyzed quantitatively. The results showed that the level of validity of the e-LKPD based on science process skills, which was 4.5, was in the valid category. So that the e-LKPD based on science process skills is valid. The benefit of this research is to see the level of accuracy or validity of teaching materials in the form of e-LKPD based on science process skills so that they can be useful for teachers and students in the learning process.